2000
DOI: 10.1016/s0042-6989(00)00039-0
|View full text |Cite
|
Sign up to set email alerts
|

Center surround receptive field structure of cone bipolar cells in primate retina

Abstract: In non-mammalian vertebrates, retinal bipolar cells show center-surround receptive field organization. In mammals, recordings from bipolar cells are rare and have not revealed a clear surround. Here we report center-surround receptive fields of identified cone bipolar cells in the macaque monkey retina. In the peripheral retina, cone bipolar cell nuclei were labeled in vitro with diamidino-phenylindole (DAPI), targeted for recording under microscopic control, and anatomically identified by intracellular staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
163
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 49 publications
(66 reference statements)
21
163
0
6
Order By: Relevance
“…Consistent with this interpretation, primate diffuse bipolar cells have center-surround receptive fields (Dacey et al, 2000a). Our results with L-AP4, however, are inconsistent with a complete separation of the ON and OFF pathways.…”
Section: Receptive Field Organizationsupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with this interpretation, primate diffuse bipolar cells have center-surround receptive fields (Dacey et al, 2000a). Our results with L-AP4, however, are inconsistent with a complete separation of the ON and OFF pathways.…”
Section: Receptive Field Organizationsupporting
confidence: 56%
“…Primate cone bipolar cells have center-surround receptive field structure (Dacey et al, 2000a). ON cone bipolar cells have an ON center response that is antagonized by simultaneous surround stimulation.…”
Section: A1 Center-surround Receptive Field Structurementioning
confidence: 99%
“…The third stimulus was a small spot (0.1 mm diameter) at higher contrast levels (0.1 or 0.3), which should generate a relatively small response in the ganglion cell but large responses in the centralmost approximately four bipolar cells. Here, we assumed that bipolar cells are spaced at ϳ30 m and have receptive fields of ϳ100 m (Dacey et al, 2000).…”
Section: Contrast Gain Control Does Not Require Inhibitory Synapsesmentioning
confidence: 99%
“…Such a synaptic mechanism would explain why one study found much stronger gain control in ganglion cell membrane potential than in bipolar cells, recorded in the same preparation (Baccus and Meister, 2002). Recordings of bipolar cells in the intact mammalian retina have been extremely limited, given the difficulty in obtaining stable recordings and identifying the bipolar cell type (Dacey et al, 2000). Here, we have shown that amacrine cell signaling is not critical for gain control, and therefore one could justify further study in the mammalian retinal slice, where identification of cone-bipolar cell types is more routine (Li and DeVries, 2006).…”
Section: Bipolar Cell Roles In Contrast Gain Control and Slow Contrasmentioning
confidence: 99%
“…Antagonistic receptive field surrounds can be detected in mammalian bipolar cells (Dacey et al, 2000). GABA released from horizontal cells onto bipolar cell dendrites could participate in this process (Yang, 2004).…”
Section: Targets For Gaba Releasementioning
confidence: 99%